Narrative Medicine: A Dimension of Hospitality in Healthcare Services: https://doi.org/10.60543/ts_iss.vi6.9406 ("Temas Sociais" Journal, 2024)
Narrative medicine, aligned with the concept of hospitality, emerges as an essential approach to humanising healthcare services. This article discusses how integrating patients' narratives into healthcare, emphasising qualified listening and valorising personal experiences and meanings, can contribute to more welcoming and patient-centred care. Through an integrative literature review, narrative medicine is explored from the hospitality perspective, highlighting the importance of empathy, an expanded understanding of the health-disease process, and the construction of bonds based on trust and reciprocity. However, challenges such as the need for greater inclusion in academic curricula and the adaptation of clinical practices to incorporate this approach are faced, aiming at promoting comprehensive care and improving the quality of assistance. This study underscores the transformative potential of narrative medicine in building a more inclusive and humanised healthcare system.
Keywords: Narrative Medicine; Hospitality; Health Humanization